Initial dynamic development of fuel spray analyzed by ultra high speed imaging. (1st April 2016) - Ding, Haichun; Wang, Ziman; Li, Yanfei; Xu, Hongming; Zuo, Chengji
Highlights: Ultra-high speed imaging was used to study near nozzle spray. Spray structures using four different fuels were examined. The formation and development of mushroom shape were discussed. Micro cone angle during the quasi-steady stage was investigated. Abstract: Effects of injection pressure and fuel thermodynamic properties on near nozzle spay patterns at the start of the fuel spray were investigated with an ultra-high speed imaging technique. Ethanol (ETH), winter fuel (WIN), diesel (REF), and Rape Methyl Ester (RME) were injected from a single-hole injector at 60 MPa, 90 MPa and 120 MPa. A long distance microscope coupled with an ultra-high speed camera (Shimadzu HPV-2) was also used. The spray structure at the start of the spray included a mushroom and a trail zone. The initial mushroom was generated by the residual fuel in the SAC volume which was responsible for the variation between the different injections. The ultra-high speed imaging revealed that delays from the start of triggering (SOT) to the emergence of liquid from the nozzle were not the same under various injection pressures for different fuels, because of their thermodynamic properties. Mushroom lengths and viscosity were closely related. RME had the longest mushroom zone while ETH had the shortest mushroom zone with no stem. At higher pressures, no ligaments were observed and the leading mushrooms were integrated into the trail zone, which can be referred to as the fully atomized region. At fully atomized regions, the increase of injection pressure did not affect spray patterns. Development of the micro cone angle during this quasi-steady stage experienced a sudden increase followed by a relatively steady stage. Injection pressure and fuel viscosity were shown to have effect on the development of spray cone angle at the opening stage.